(untitled) (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: The study aimed to develop and assess an Android app designed for farmers with a low educational status that can formulate a least-cost ration. Materials and Methods: First, a computer-android-based app named BLRI FeedMaster was developed to guide users in formulating a balanced ration at the least cost. A survey was conducted on 30 livestock officers and 18 farmers with 50 cattle to evaluate its efficacy at the field level. The study outcomes were milk yield, feeding cost, milk composition, time, and cost for management before and after using the BLRI FeedMaster app. Descriptive statistics and paired sample t-tests were used to analyze the data. Results: After adopting the BLRI FeedMaster app, a significant increase was observed in daily average milk yield (9.39 ± 0.32 l from 8.37 ± 0.36 l), while a considerable decrease was observed in daily average feed quantity (4.88 ± 0.15 kg from 5.60 ± 0.17 kg) and feed cost (BDT 28.00 ± 0.50 from BDT 29.75 ± 0.49). Besides, the number of visits, time, and cost for seeking professional services regarding feed, health care, and other information was significantly minimized. The number of visits decreased to 0.36 ± 013 from 3.07 ± 0.38, and the consumed time was reduced from 270 ± 34.30 to 235.71 ± 59.42 min (p < 0.05) after adopting the app. Conclusion: Hence, this app was very beneficial for farmers with a low economic and educational background and may ultimately help farmers with profitable animal farming and sustainable production in the least developed countries like Bangladesh. J. Adv. Vet. Anim. Res., 9(3): 374–382, September 2022 http://doi.org/10.5455/javar.2022.i605